ENHANCING ROAD PERFORMANCE MEASUREMENT IN INDONESIA: PROPOSED CHANGES AND FUTURE DIRECTIONS - Sita, Tisara; Mulyono, Agus Taufik; Utomo, Suryo Hapsoro Tri (Journal of Applied Engineering Science, 2023)
This research aims to evaluate the fulfillment criteria of road performance indicators in the current long segment scheme in Indonesia by considering road performance indicators in other countries in PMBC. The research utilized the Confirmatory Factor Analysis (CFA) model in Structural Equation Modeling (SEM). The respondents were service providers and users, and the sampling technique was random. The study found that all significant road performance indicators affect the latent variable, based on the evaluation of road performance indicators listed in the 2018 Revision 2 General Specification of the Ministry of Public Works and Housing that are currently in effect. The CFA on 40 road performance indicators indicates that nine indicators do not have a significant influence on road performance. Therefore, only 31 indicators are proposed concerning response time. In addition, new road performance indicators, such as uneven patching, raveling, and dirty drainage, are proposed to be included. Response time to the indicators also needs to be updated based on service users’ and providers’ questionnaire survey results. This study provides valuable information for policymakers and stakeholders to improve road preservation outcomes in Indonesia.